The role of senescence, telomere dysfunction and shelterin in vascular aging. (12th September 2018) - Liu, Yu; Bloom, Samuel I.; Donato, Anthony J.
Abstract: In the United States and other westernized nations, CVDs are the leading cause of death in adults over 65 years of age. Large artery stiffness and endothelial dysfunction are increased with age and age‐associated arterial dysfunction is an important antecedent of CVDs. One age‐associated change that may contribute to vascular dysfunction and CVD risk is an increase in the number of resident senescent cells in the vasculature. Senescent cells display a pro‐oxidant, pro‐inflammatory phenotype known as the SASP. However, the mechanisms that drive the SASP and the vascular aging phenotype remain elusive. A putative mechanism is the involvement of oxidative stress and inflammation in telomere function. Telomeres are the end caps of chromosomes which are maintained by a six‐protein complex known as shelterin. Disruption of shelterin can uncap telomeres and induce cellular senescence. Accordingly, in this review, we propose that oxidative stress and inflammation disrupt shelterin in vascular cells, driving telomere dysfunction and that this mechanism may be responsible for the induction of SASP. The proposed mechanisms may represent some of the initial changes that lead to vascular dysfunction in advanced age.